2016
DOI: 10.1242/dmm.021766
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mitochondrial transport and morphology as early pathological changes in human models of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA), characterized by specific degeneration of spinal motor neurons, is caused by mutations in the survival of motor neuron 1, telomeric (SMN1) gene and subsequent decreased levels of functional SMN. How the deficiency of SMN, a ubiquitously expressed protein, leads to spinal motor neuron-specific degeneration in individuals affected by SMA remains unknown. In this study, we examined the role of SMN in mitochondrial axonal transport and morphology in human motor neurons by generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
6
52
0
Order By: Relevance
“…Consequently, SMN deficiency may impair targeting and local translation of axonal mRNAs essential for motor neuron development and maintenance 44, 45. Furthermore, SMN regulates several other fundamental cellular processes in the neuronal cytoplasm that are critical for maintaining axonal and synaptic health, including endocytic pathways, local translation, mitochondrial transport, and targeting to axons and ubiquitin homeostasis 46, 47, 48, 49, 50, 51…”
Section: How Low Levels Of Smn Cause Smamentioning
confidence: 99%
“…Consequently, SMN deficiency may impair targeting and local translation of axonal mRNAs essential for motor neuron development and maintenance 44, 45. Furthermore, SMN regulates several other fundamental cellular processes in the neuronal cytoplasm that are critical for maintaining axonal and synaptic health, including endocytic pathways, local translation, mitochondrial transport, and targeting to axons and ubiquitin homeostasis 46, 47, 48, 49, 50, 51…”
Section: How Low Levels Of Smn Cause Smamentioning
confidence: 99%
“…Using live cell imaging of motor neurons derived from SMA type 1 iPSCs, Xu et al (2016) found a reduction in size, number and axonal transport of mitochondria in the SMA cells compared to WT cells. NAC treatment returned mitochondrial numbers and transport to WT levels.…”
Section: Hypoxic Stressmentioning
confidence: 99%
“…Interestingly, we have observed the axonal transporter defects in spinal muscular atrophy (SMA) iPSC-derived motor neurons (Xu et al, 2016). Spinal muscular atrophy (SMA), the leading genetic cause of death in infants and toddlers, is caused by homologous deletion or mutations of the survival of motor neuron 1 ( SMN1 ) gene (Lefebvre et al, 1995).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Spinal motor neurons are specifically degenerated in SMA, yet the underlying mechanisms are not known. Using human pluripotent stem cell-based SMA cell models, we observed early mitochondrial defects in spinal motor neurons (Wang et al, 2013b, Xu et al, 2016), which is implicated in the specific degeneration of spinal motor neurons in SMA. Interestingly, mitochondrial dysfunction has also been as a major pathological process in many other neurodegenerative diseases, such as ALS, Parkinson’s disease, and Huntington’s disease (Chen and Chan, 2009, Magrane et al, 2014).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%